Plasma Angiotensin II Is Increased in Critical Coronavirus Disease 2019 - Camargo, Rafael L.; Bombassaro, Bruna; Monfort-Pires, Milena; Mansour, Eli; Palma, Andre C.; Ribeiro, Luciana C.; Ulaf, Raisa G.; Bernardes, Ana Flavia; Nunes, Thyago A.; Agrela, Marcus V.; Dertkigil, Rachel P.; Dertkigil, Sergio S.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) employs angiotensin-converting enzyme 2 (ACE2) as its receptor for cell entrance, and studies have suggested that upon viral binding, ACE2 catalytic activity could be inhibited; therefore, impacting the regulation of the renin-angiotensin-aldosterone system (RAAS). To date, only few studies have evaluated the impact of SARS-CoV-2 infection on the blood levels of the components of the RAAS. In this study, we determined blood levels of ACE, ACE2, angiotensin-II, angiotensin (1-7) and angiotensin (1-9) at hospital admission and discharge in a group of patients presenting with severe or critical evolution of coronavirus disease 2019 (COVID-19). We showed that ACE, ACE2, angiotensin (1-7) and angiotensin (1-9) were similar in critical and severe COVID-19 patients. However, at admission, angiotensin-II levels are significantly higher in patients presenting as critical, compared to patients presenting with severe COVID-19. We propose that early measurement of Ang-II could be a useful biomarker for identifying patients at higher risk for extremely severe progression of the disease.